Gender Differences in Intra-articular and Extra-articular Injuries Associated with Acute Anterior Cruciate Ligament Ruptures - Tan, Si Heng Sharon; Kripesh, Aishwarya; Chan, Chloe Xiaoyun; Krishna, Lingaraj (The Journal of Knee Surgery, 2019)
Females are well known to have a two to nine times increase in relative risk of anterior cruciate ligament (ACL) rupture as compared with males. However, there is limited literature available regarding the rates of associated intra-articular and extra-articular injuries associated with ACL ruptures. The purpose of this study was to investigate the gender differences in intra-articular and extra-articular injuries associated with ACL ruptures in an acute setting. Therefore, in the cross-sectional study of consecutive patients, all patients who underwent ACL reconstruction in a single institution were identified if they had a magnetic resonance imaging (MRI) done within 6 weeks of sustaining the injury and if their injury was sustained during sports activities. Patients were excluded if they had prior surgery in the affected knee, including revision ACL reconstructions. A musculoskeletal MRI radiologist blinded to the study's purpose then reported the incidence of ligamentous injuries, meniscal tears, chondral injuries, and bone contusions. Correlations were then performed between the patient's gender and the prevalence of these associated injuries. A total of 304 patients were included in the study. Comparison between males and females revealed no gender differences for the associated intra-articular and extra-articular injuries of acute ACL rupture. These include the prevalence of medial collateral ligament injuries (p = 0.118), lateral collateral ligament injuries (p = 0.445), medial meniscus injuries (p = 0.874), lateral meniscus injuries (p = 0.612), chondral injuries (p = 0.331), medial (p = 0.143) and lateral femoral condyle bone contusions (p = 0.246), and medial (p = 0.787) and lateral tibial plateau bone contusions (p = 0.765). In conclusion, males and females have similar rates of associated intra-articular and extra-articular injuries after ACL rupture in the acute setting. These include associated collateral ligament injuries, meniscal injuries, chondral injuries, and bone contusions. The level of evidence is Level II.
Keywords: anterior cruciate ligament; ligament; meniscus; chondral; bone contusion